Pendampingan Pastoral Orang Sakit Di Paroki Santa Maria Immaculata Wayun Palu Rejo - Prosper Derico Antonio Gepa; Silvester Adinuhgra; Paulina Maria Ekasari Wahyuningrum (Sepakat : Jurnal Pastoral Kateketik, 2023)
This study aims to describe the Pastoral Assistance of the Sick in Santa Maria Immaculata Wayun Palu Rejo Parish. This research departs from efforts and forms of pastoral care for others who are suffering from illness. The Church as God's people becomes an intermediary that presents the faith encounter of the sick with God, through pastoral care for the sick. This study uses a descriptive qualitative approach to provide an in-depth description of the pastoral care for the sick at Santa Maria Immaculata Wayun Palu Rejo Parish. The data in this study were collected using the interview method which was conducted together with 4 neighborhood leaders, 3 sick people's families, 2 categorical groups, 1 nurse and 1 priest. Furthermore, the data obtained was then analyzed using the "Miles and Huberman" analysis method, which was divided into three levels, namely reduction, data presentation, and drawing conclusions. Based on the results of the study, it was concluded that pastoral care for the sick at Santa Maria Immaculata Parish Wayun Palu Rejo has been running and implemented but it can be said that it has not been very effective. This conclusion is based on the statement of an informant who revealed that there are still people who do not have awareness about pastoral care for sick people and there are still families of sick people who believe in supernatural things and traditional healers to cure illnesses.